W trosce o zdrowie psychiczne młodzieży – pomiędzy dialogiem a biblioterapią - Kociołek, Roksana; Janowiec, Anna; Majcher, Agnieszka (2016)
Care about the mental health of youth – between dialogue and bibliotherapy. The article describes the promotion of mental health among young people undertaken by members of the Institute of Social Therapy and Education – Association based on the original screenplay of classes using bibliotherapy techniques.
Keywords: bibliotherapy; mental health; mental health promotion; health education; youth